1998
DOI: 10.1128/jvi.72.9.7191-7200.1998
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Defective Poliovirus RNA Replication by 3AB-Containing Precursor Polyproteins

Abstract: This study demonstrates the in vitro complementation of an RNA replication-defective lesion in poliovirus RNA by providing a replicase/polymerase precursor polypeptide [P3(wt) {wild type}] in trans. The replication-defective mutation was a phenylalanine-to-histidine change (F69H) in the hydrophobic domain of the membrane-associated viral protein 3AB. RNAs encoding wild-type forms of protein 3AB or the P3 precursor polypeptide were cotranslated with full-length poliovirus RNAs containing the F69H mutation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Attempts to rescue 3C L70P mutant PV by trans-complementation with recombinant adenovirus expressing wild-type 3C also failed. This is not surprising as earlier work has also indicated that trans-complementation of defective PV with proteins supplemented from heterologous systems is unproductive (Towner et al, 1998;Cornell et al, 2004) and it appears that the catalytic activity of 3C in processing the P1 structural region is dependent on it being expressed as 3CD rather than 3C alone, both in vitro and in vivo (Jore et al, 1988;Ypma-Wong et al, 1988). However, 3C L70P mutant plasmid could trans-complement a 1AB deletion plasmid, resulting in production of a virus population, which contained both wild-type and deletion mutants of 1AB gene.…”
Section: Sequence Alignment Of 3c Proteasesmentioning
confidence: 78%
“…Attempts to rescue 3C L70P mutant PV by trans-complementation with recombinant adenovirus expressing wild-type 3C also failed. This is not surprising as earlier work has also indicated that trans-complementation of defective PV with proteins supplemented from heterologous systems is unproductive (Towner et al, 1998;Cornell et al, 2004) and it appears that the catalytic activity of 3C in processing the P1 structural region is dependent on it being expressed as 3CD rather than 3C alone, both in vitro and in vivo (Jore et al, 1988;Ypma-Wong et al, 1988). However, 3C L70P mutant plasmid could trans-complement a 1AB deletion plasmid, resulting in production of a virus population, which contained both wild-type and deletion mutants of 1AB gene.…”
Section: Sequence Alignment Of 3c Proteasesmentioning
confidence: 78%
“…A much more efficient rescue of lesions in the 3AB coding sequence was reported by Towner et al (1998), who used the cell-free system of poliovirus replication developed by Molla et al (1991). Apparently, the supply in trans of P3 polypeptides in vitro is more efficient that in vivo, a phenomenon that remains as yet unexplained.…”
Section: General Observations Of Picornavirus Complementationmentioning
confidence: 92%
“…Moreover, the novel approach can be used to study individual steps of viral replication in the absence of cell-membrane barriers. Several interesting observations regarding protein-protein interactions, the role of membranes, of cellular membranous components or soluble cellular factors, or of inhibitors of viral RNA synthesis, have been published (Barton and Flanegan, 1993;Molla et al, 1993cMolla et al, , 1994Barton et al, 1995;Parsley et al, 1997;Cuconati et al, 1998;Towner et al, 1998). The use of the cell-free cellular extract for studies of poliovirus RNA replication, however, is still in the early stages of exploitation.…”
Section: Cell-free De Novo Synthesis Of Poliovirusmentioning
confidence: 99%
“…This has been attributed to insufficient concentrations of viral proteins for RNA synthesis or encapsidation, to differences in membranous structures or the instability of viral particles in vitro [ 3 , 5 ]. With the large amount of input RNA the level of translation in vitro is relatively high from the beginning of incubation and hence complementation between viral proteins is more efficient than in vivo [ 6 , 7 ]. We have recently observed that in vitro translation-RNA replication reactions, programmed with viral RNA, contain suboptimal concentrations of the important viral precursor protein 3CD pro for efficient virus production.…”
Section: Introductionmentioning
confidence: 99%